Role of rehabilitation in patients with hypertension - Michalik, Joanna; Wawryszuk, Marta; Wolski, Dariusz; Stanisławek, Andrzej; Węgorowski, Paweł (Journal of Education, Health and Sport, 2017)
Admission Hypertension is a disease of the civilization. The prevalence of this disease in the Polish population ranges up to 30% and its prevalence increases with age. Comprehensive rehabilitation allows treatment in all areas of the patient's life that may affect his or her illness. It depends not only on the use of pharmacological or dietary treatment but also includes physical and psychosocial rehabilitation. Integration of all these elements allows the patient to be surrounded by professional treatment. Purpose of research The main purpose of the work is to define the role of rehabilitation in the treatment of patients with hypertension. Materials and Methods The test material is information obtained through an anonymous questionnaire, and the method is a diagnostic survey. The research was conducted at the Specialist Hospital in Biała Podlaska and the Regional Specialist Hospital in Lublin. Participation in the study was voluntary and anonymous, with a willingness to commit 50 people. Conclusions The results show that patients are aware of the severity of their disease and the need for change, as only 3% of the patients have not made any changes since the onset of hypertension. Among those who implemented the change, 56% of respondents noted the effects of lifestyle modification and the impact of the rehabilitation process. Discussion Respondents reported that they had noticed the positive effects of rehabilitation: they felt more comfortable after the procedure, reduced weight, began to modify their diet, and sometimes returned to work. Patients feel the need for change and their awareness of the contribution of rehabilitation in the healing process. Key words: hypertension, rehabilitation, lifestyle